Evaluation of a peer‐led self‐management education programme PEP Talk: Diabetes, Healthy Feet and You. Issue 6 (25th November 2013) - Woodbury, M. Gail; Botros, Mariam; Kuhnke, Janet L.; Greene, Julie
Abstract PEP (Peer Education Programme) Talk: Diabetes, Healthy Feet and You is a peer‐led self‐management programme developed to address the problems of growing prevalence of diabetes and its complications, and limited health care dollars. An evaluation of the programme, how it might be situated within a public health perspective and potential bridges for its implementation in communities throughout Canada and worldwide, are presented. The programme consisted of workshops that were conducted by volunteer peer leaders and health care professionals in 12 communities in 10 Canadian provinces; the volunteers were supported through monthly mentoring teleconferences, on‐line tips and discussion board conversations. A web portal was developed to be used by the team, volunteers and community participants. Workshop curriculum was developed based on diabetes footcare and self‐management best practise guidelines. Community participants answered pre‐and post‐workshop statements that indicated that learning occurred, as indicated by an increase in the number of statements answered correctly. Participants' feedback about the workshops was positive. In telephone follow‐up interviews, 97% of respondents reported having changed their foot self‐management behaviours. The portal was commonly used according to website visits, but not as much as expected for registration of community participants. It is recommended that this programme be made widely available and tailored to the specific needs of the communities and that further evaluation be conducted.